The secret agent a simple tale - Conrad, Joseph (New York Doubleday, Page & Co, 1921)
In the only novel Conrad set in London, The Secret Agent communicates a profoundly ironic view of human affairs. The story is woven around an attack on the Greenwich Observatory in 1894 masterminded by Verloc, a Russian spy working for the police, and ostensibly a member of an anarchist group in Soho. His masters instruct him to discredit the anarchists in a humiliating fashion, and when his evil plan goes horribly awry, Verloc must deal with the repercussions of his actions. While rooted in the Edwardian period, Conrad's tale remains strikingly contemporary, with its depiction of Londoners gripped by fear of the terrorists living in their midst.
Includes index
Keywords: Conspiracies--Fiction.